Continuity and change: land and water use reforms in rural Uzbekistan. Socio-economic and legal analyses for the region Khorezm - Peter Wehrheim; Anja Schoeller-Schletter; Christopher Martius (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2008)
Decades of Soviet rule have left a heritage of environmental and social problems in Central Asia. The demise of an entire ecosystem at unprecedented pace, the 'Aral Sea Syndrome', is the most prominent of the undesired outcomes of the focus on agricultural production that has dominated land and resource use and continues till today. The international outcry over this ecological crisis has delegated other - and maybe more urgent - problems to a second pane. Rural livelihoods are rapidly deteriorating, unemployment is high, and rural poverty widespread. Ecological aspects, although strongly affecting everyday life in rural areas - such as water and soil salinity and environmental pollution - are not the fore most concern to the local population, as the economic survival is the more pressing need. Nevertheless, it is exactly in this situation where the larger part of the population exploits the natural resources further rather than preserving the ecological basis as a natural means of the local land's productivity. Table of contents: Preface and acknowledgements; Peter Wehrheim, Anja Schoeller-Schletter, Christopher Martius. Chapter 1: Farmers, cotton, water, and models - Introduction and overview; Peter Wehrheim, Christopher Martius. Chapter 2: Organizing agricultural production - Law and legal forms in transition; Anja Schoeller-Schletter. Chapter 3: A model-based analysis of land and water use reforms in Khorezm: Effects on different types of agricultural producers; Nodir Djanibekov. Chapter 4: Optimal crop allocation and consequent ecological benefits in large scale (shirkat) farms in Uzbekistan's transition process; Ihtiyor Bobojonov, Inna Rudenko, John P. A. Lamers. Chapter 5: Where has all the water gone? Marc Müller. Chapter 6: Analysis of water use and allocation for the Khorezm region in Uzbekistan using an integrated economic-hydrologic model; Tina Schieder, Ximing Cai. Chapter 7: Problems and perspectives of water user associations in Uzbekistan; Darya Hirsch (Zavgorodnyaya). Chapter 8: Barriers to technological change and agrarian reform in Khorezm, Uzbekistan; Caleb Wall. Chapter 9: Analysis of agricultural markets in Khorezm, Uzbekistan; Ihtiyor Bobojonov, John P. A. Lamers. Chapter 10: Cotton, agriculture, and the Uzbek government; Marc Müller
urn:nbn:de:gbv:3:2-7987
Keywords: 330